Revisiting the Career Anchor Model: A Proposition and an Empirical Investigation of a New Model of Career Value Structure - Wils, Thierry; Wils, Laura; Tremblay, Michel (Relations industrielles / Industrial Relations, 2014)
This study proposes an original model of career values organized in a circular logic. The new career value structure consists of four quadrants opposed in pairs (bureaucratic self-concept versus protean self-concept, and careerist self-concept versus social self-concept). Contrary to Schein’s model, which rests on the dominance of a single career anchor, our model organizes career anchors according to attraction and repulsion, which may explain the existence of several dominant anchors.Based on a sample of 240 employees and 155 managers in the healthcare sector, a new instrument to measure career values was validated. Four quadrants emerged from the multidimensional analysis. Hypotheses regarding the links between quadrants of career values and career anchors were largely supported by multiple regression analysis. Notably, the managerial career anchor is significantly linked to the careerist self-concept, whereas the service anchor is significantly associated with the social self-concept. The study also affirmed hypotheses linking the quadrants to other variables like collectivism and proactive behaviors. Accordingly, collectivism is significantly linked to the social self-concept, whereas proactive behaviors are connected to the protean self-concept. Not only was the structure model verified empirically, but the construct validity of the new instrument was also demonstrated. This study also clarifies several problems related to career anchors, such as career anchor structures or ambiguity inherent in some career anchor measurement indicators.